ANALISA KELENGKAPAN PENGISIAN RESUME MEDIS DI RUMAH SAKIT UMUM UNIVERSITAS KRISTEN INDONESIA JAKARTA - Indah Kristina; Syafira maulita nur afifah (APIKES Bhumi Husada Jakarta, 2022)
ABSTRACT A medical resume is a summary of medical service activities provided by health workers, especially doctors during the treatment period until the patient is discharged, either alive or dead. The content of the medical resume must be complete and concise. The impact of incomplete medical resume shows care information during treatment is incomplete and correct. This includes billing health care costs to the insurance company. The purpose of the study was to get an overview of the completeness of filling out the patient's medical resume at the General Hospital of the Christian University of Indonesia.The research method used is descriptive method, with a population of 188 medical resumes and a sample of 128 medical resumes for the April 2021 period. The data collection technique is observation using a checklist which includes patient identity, important notes, authentication, and good record keeping.Based on the results of the study, it can be concluded that the General Hospital of the Indonesian Christian University does not have a standard operating procedure for filling out medical resume forms. Of the 128 samples of complete medical resume forms, 113 (88%) and 15 (12%) medical resume forms were incomplete. The incompleteness factor in filling out the medical resume form was caused by the non-existent standard operating procedure for filling out the medical resume, the lack of socialization on the importance of filling out the medical resume form completely. It is necessary to issue standard operating procedures for filling out medical resume forms, socializing to doctors as the person in charge of patient care, checking the filling of medical resume forms before patients go home. Key words : Completeness analysis of medical resume. ABSTRAK Resume medis merupakan ringkasan kegiatan pelayanan medis yang diberikan tenaga kesehatan khususnya dokter selama masa perawatan hingga pasien keluar baik dalam keadaan hidup maupun meninggal. Isi resume medis harus lengkap dan singkat. Dampak dari ketidaklengkapan resume medis menunjukkan informasi asuhan selama perawatannya tidak lengkap dan benar. Termasuk untuk penagihan biaya pelayanan Kesehatan ke pihak asuransi. Tujuan Penelitian adalah Mendapat gambaran kelengkapan pengisian resume medis pasien di Rumah Sakit Umum Universitas Kristen Indonesia. Metode penelitian yang digunakan adalah metode deskriptif, dengan populasinya adalah 188 resume medis dan sampel yang didapat sebanyak 128 resume medis periode April 2021. Teknik pengumpulan data adalah observasi menggunakan checklist yang meliputi identitas pasien, catatan penting, autentifikasi, dan pencatatan yang baik. Berdasarkan hasil penelitian, dapat disimpulkan bahwa Rumah Sakit Umum Universitas Kristen Indonesia tidak memiliki Standar Prosedur operasional pengisian formulir resume medis. Dari 128 sampel formulir resume medis terisi lengkap sebanyak 113 (88%) dan 15 (12%) formulir resume medis tidak terisi lengkap. Faktor ketidaklengkapan pengisian formulir resume medis disebabkan oleh standar prosedur operasional pengisian resume medis tidak ada, kurangnya sosialisasi terhadap pentingnya pengisian formulir resume medis dengan lengkap. Perlu di terbitkan standar prosedur operasional pengisian formulir resume medis, mensosialisasikan kepada dokter sebagai penanggung jawab pelayanan pasien, melakukan pengecekkan pengisian formulir resume medis sebelum pasien pulang. Kata kunci : Analisa Kelengkapan resume medis.